Interdisciplinary approach: practices for training for health care workers addressing child sex trafficking cases - Vasquez, Erica, author; Buchan, Victoria, advisor; Tungate, Susan, committee member; Unnithan, Prabha, committee member; Gandy, John, committee member (Colorado State University. Libraries, 2024)
Commercial sexual exploitation of children (CSEC) remains a significant public health concern in the United States (Gibbons & Stoklosa, 2016). Many CSEC victims receive medical care at some point during exploitation for the treatment of acute care. Scholars lack reliable statistics on CSEC occurrences due to the lack of data, criminal activity, victims not recognized by professionals, and other factors (Greenbaum et al., 2018). Sex exploitation of children is not limited to any particular ethnic, racial, or socioeconomic group; however, children from lower socioeconomic groups are at risk (Ark of Hope for Children, 2019). This study was a grounded theory study. The researcher identified current ways ED hospital setting health care workers engage, identify, assess, and provide services/interventions and resources for child sex trafficked victims along with their recommendations/suggestions for a future sex trafficking training. An Integrated Anti-Child Sex Trafficking Conceptual Framework was also developed. Semi-structured interviews were used with open-ended questions along with a survey. Theoretical sampling and snowball sampling were used to select participants. The researcher interviewed eight nurses and seven social workers who have currently worked with or may have worked with female child sex trafficking victims in emergency department (ED) hospital settings.
Keywords: emergency department settings; health care workers; trauma informed care; grounded theory; child sex trafficking; integrated health care